Optimized Peptide–MHC Multimer Protocols for Detection and Isolation of Autoimmune T-Cells - Dolton, Garry; Zervoudi, Efthalia; Rius, Cristina; Wall, Aaron; Thomas, Hannah L.; Fuller, Anna; Yeo, Lorraine; Legut, Mateusz; Wheeler, Sophie; Attaf, Meriem; Chudakov, Dmitriy M.; Choy, Ernest; et al. (Frontiers in Immunology, 2018)
Peptide-MHC (pMHC) multimers have become the 'gold standard' for the detection and isolation of antigen-specific T-cells but recent evidence shows that normal use of these reagents can miss fully functional T-cells that bear T-cell receptors (TCRs) with low affinity for cognate antigen. This issue is particularly pronounced for anti-cancer and autoimmune T-cells as self-reactive T-cell populations are enriched for low affinity TCRs due to the removal of cells with higher affinity receptors by immune tolerance mechanisms. Here, we stained a wide variety of self-reactive human T-cells using regular pMHC staining and an optimised technique that included: (i) protein kinase inhibitor (PKI), to prevent TCR triggering and internalization; and, (ii) anti-fluorochrome antibody to reduce reagent dissociation during washing steps. Lymphocytes derived from the peripheral blood of type 1 diabetes patients were stained with pMHC multimers made with epitopes from preproinsulin (PPI), insulin-β chain, Glutamic acid decarboxylase 65 (GAD65) or glucose-6-phospate catalytic subunit-related protein (IGRP) presented by disease-risk allelles HLA A*0201 or HLA*2402. Samples from ankylosing spondylitis patients were stained with a multimerised epitope from vasoactive intestinal polypeptide receptor 1 (VIPR1) presented by HLA B*2705. Optimised procedures stained an average of 40.5-fold (P=0.01, range between 1.4 and 198) more cells than could be detected without the inclusion of PKI and cross-linking anti-fluorochrome antibody. Higher order pMHC dextramers recovered more cells than pMHC tetramers in parallel assays, and standard staining protocols with pMHC tetramers routinely recovered less cells than functional assays. HLA A*0201-restricted PPI-specific and HLA B*2705-restricted VIPR1-specific T-cell clones generated using the optimised procedure could not be stained by standard pMHC tetramer staining. However, these clones responded well to exogenously supplied peptide and endogenously processed and presented epitopes. We also showed that anti-fluorochrome antibody-conjugated magnetic beads enhanced staining of self-reactive T-cells that could not be stained using standard protocols, thus enabling rapid ex vivo isolation of autoimmune T-cells. We therefore conclude that regular pMHC tetramer staining is generally unsuitable for recovering self-reactive T-cells from clinical samples and recommend the use of the optimised protocols described herein.